Agresión y estrés laboral en conductores de transporte urbano en Tunja (2020)
The objective of this research was to determine the relationship between aggression and work stress in urban transport drivers of the City of Tunja. A cross-sectional study was conducted with a non-probabilistic sample of 75 individuals aged between 28 and 65 years, with at least one year of experience in the company. The measurement of stress was made through the application of the stress assessment questionnaire revalidated by the Javeriana University (2010) and the Ministry of Social Protection, which contains questions related to physiological, intellectual and occupational symptoms of social and psycho-emotional behavior. Likewise, the inventory of aggressive situations and behaviors and the inventory of motivators for the aggression validated by (Acosta & Hernandez, 2008) were applied. The results indicate a positive correlation between stress categories and aggressive behavior patterns, however, stress levels according to the Likert scale scored very low. The ISCA and IMA inventories revealed that the most frequent types of aggression in this sample were verbal aggression and not being able to collaborate. According to the ISCA situations subscale, it indicates that the scenarios in which these types of aggression are mostly presented are related to labor and family economy problems. The Inventory of Motives for Aggression (IMA) shows that the participants were motivated to carry out aggressive acts under the premise that it is necessary to defend values and ideas and that they should be respected.